Revue historique e revue de synthèse historique: o caso A. D. Xénopol - Borges, Clayton Ferreira e Ferreira (2013)
´This study aims to investigate the theory of the history of Romanian philosopher and historian Alexandru Dimitrie Xénopol from their articles published in the Revue Historique Synthèse between the years 1900 and 1914. Xénopol developed a theory of history based on its own classification of the sciences, where the characterization of facts formed the basis for a definition of the scientific character of the story, as a particular science where the notion of time owned a primary importance. Your requirement historicization of historical facts at a given time and place has consequently a greater emphasis on categories of change, evolution, development and transformation, these categories constitute a crucial dimension, the one that would interest will analyze the historical facts by history science.